Low-dose interleukin-2 therapy: a promising targeted therapeutic approach for systemic lupus erythematosus. Issue 2 (22nd March 2023) - Akbarzadeh, Reza; Riemekasten, Gabriela; Humrich, Jens Y.
Abstract : Purpose of review: Low-dose interleukin-2 (IL-2) therapy is increasingly recognized as a promising novel therapeutic concept in inflammatory and autoimmune diseases, in particular in systemic lupus erythematosus (SLE). As IL-2 is indispensable for the growth and survival of regulatory T cells (Treg), deficiency of this regulatory cytokine plays a significant role in immune dysregulation and breach of tolerance in SLE. Recovery of Treg activity by low-dose IL-2 therapy directly interferes with the immune pathology in SLE and thus can be considered a targeted treatment approach with a unique and physiological mode of action. Recent findings: In this review, the pathophysiological rationales behind the concept of low-dose IL-2 therapy in SLE will be explained and major advances in translational research and the clinical development of low-dose IL-2 therapy focusing on the results from two recent, randomized and placebo-controlled phase 2 trials will be highlighted. Summary: Several clinical studies including two recent randomized trials have proven the very good safety profile of low-dose IL-2 therapy and its capability to selectively recover and expand the Treg population in patients with active SLE. Given the emerging evidence for the clinical potential of low-dose IL-2 therapy in SLE, these studies strongly confirm the pathophysiological concept behind this targeted therapeutic approach in SLE and provide a robust basis for establishing further in-depth and confirmatory clinical trials testing the application of low-dose IL-2 in SLE and other autoimmune diseases.